The Influence of Teacher and Students Errors Correction Techniques on Students’ Achievement in English at College of Physical Education for Women (Journal of the College of Education for Women, 2019)
The research is an attempt to investigate experimentally the influence of teacher’s errors correction and students’ errors correction on teaching English at the College of Physical Education for Women. Errors are seen as a natural way for developing any language but teachers are puzzled the way they can correct these errors. So, this research gives some idea of using two types of errors correction. The sample of the research is female students of the first year stage at the College of Physical Education for Women of the academic year 2009-2010. The whole population of the research is (94) students while the sample is (64). Thus, the sample represents 68% from the population of the research. The sample represents It is hypothesized that there are no significant differences between the experimental group which has been taught according students’ errors correction technique and the control group which has been taught according the teacher’s error correction technique in teaching English. To fulfill the aim of the research an experiment has been designed with two groups of (64) students chosen randomly from first year students. Both groups have matched in terms of age, the level of subjects’ achievement in previous year (the Baccalaureate Exam), and the academic type of study in the secondary school. The experiment lasted nine weeks. A post-test has been constructed in the last week for both groups after insuring its validity and reliability. After analyzing the results statistically, it has been found that there are significant differences between the two groups in their achievement in the test. Accordingly, the null hypothesis has been rejected. Finally, instructors are recommended to use students’ correction errors for developing their students’ achievement and knowledge in English language.